The Locus of Control Issue in Standards-Based Accountability - Larry McNeal; W. Keith Christy (Educational Considerations, 2003)
Many states have developed complex approaches to standards-based accountability because both policymakers and educators recognize that accountability requires credible assessment tasks – tasks that clearly reflect the language of the standards and that articulate good classroom instruction.